2020
DOI: 10.3390/genes11040440
|View full text |Cite
|
Sign up to set email alerts
|

LRRC19—A Bridge between Selenium Adjuvant Therapy and Renal Clear Cell Carcinoma: A Study Based on Datamining

Abstract: Kidney renal clear cell carcinoma (KIRC) is the most common and fatal subtype of renal cancer. Antagonistic associations between selenium and cancer have been reported in previous studies. Selenium compounds, as anti-cancer agents, have been reported and approved for clinical trials. The main active form of selenium in selenoproteins is selenocysteine (Sec). The process of Sec biosynthesis and incorporation into selenoproteins plays a significant role in biological processes, including anti-carcinogenesis. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…[27][28][29] Similarly, the other IRGMS mentioned in this study have also been shown to be strongly associated with various tumors in previous studies. [30][31][32][33][34][35][36][37][38][39][40][41] 5 Conclusion…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29] Similarly, the other IRGMS mentioned in this study have also been shown to be strongly associated with various tumors in previous studies. [30][31][32][33][34][35][36][37][38][39][40][41] 5 Conclusion…”
Section: Discussionmentioning
confidence: 99%
“…The protein product of LRRC19 is specifically expressed in the kidney, spleen, and intestine and is involved in local inflammatory responses ( 70 ). In addition, LRRC19 is associated with the prognosis and adjuvant treatment of ccRCC ( 71 , 72 ). As a member of the prominin family, PROM1 is often considered a biomarker for cancer stem cells ( 73 ).…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that the LRRC19 protein appears to be specifically expressed in the kidney, spleen, and intestine [ 31 ]. Liu et al reported that the reduced expression of LRRC19 was an independent risk factor for OS and LRRC19 could serve as a novel biomarker for prognosis and adjuvant treatment of selenium [ 32 ]. Chai et al proposed that LRRC19 can activate NF-kB and induce the expression of pro-inflammatory cytokines and is involved in the response to local inflammation [ 31 ].…”
Section: Discussionmentioning
confidence: 99%